A portable digital speech-rate converter for hearing impairment - Nejime, Y.; Aritsuka, T.; Imamura, T.; Ifukube, T.; Matsushima, J. (IEEE transactions on rehabilitation engineering, 1996)
A real-time hand-sized portable device that slows speech speed without changing the pitch is proposed for hearing impairment. By using this device, people can listen to fast speech at a comfortable speed. A combination of solid-state memory recording and real-time digital signal processing with a single chip processor enables this unique function. A simplified pitch-synchronous, time-scale-modification algorithm is proposed to minimize the complexity of the DSP operation. Unlike the traditional algorithm, this dynamic-processing algorithm reduces distortion even when the expansion rate is only just above 1. Seven out of 10 elderly hearing-impaired listeners showed improvement in a sentence recognition test when using speech-rate conversion with the largest expansion rate, although no improvement was observed in a word recognition test. Some subjects who showed large improvement had limited auditory temporal resolution, but the correlation was not significant. The results suggest that, unlike conventional hearing aids, this device can be used to overcome the deterioration of auditory ability by improving the transfer of information from short-term (echoic) memory into a more stable memory trace in the human auditory system.